Dead girls don't write letters - Giles, Gail. (Brookfield, CT : Roaring Brook Press, 2003)
Fourteen-year-old Sunny is stunned when a total stranger shows up at her house posing as her older sister Jazz, who supposedly died out of town in a fire months earlier.
550
Accelerated Reader AR
Keywords: Sisters -- Juvenile fiction; Death -- Juvenile fiction; Mystery fiction